Opportunities for Developing Students’ Speech in a Digital Learning Environment - Abdurakhmonova Munira (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article explores the opportunities for developing students’ speech in a digital learning environment. It analyzes how modern digital tools such as interactive platforms, e-learning resources, and multimedia technologies contribute to improving learners’ speaking skills. The study highlights that digital learning environments increase student engagement, provide interactive communication opportunities, and support individualized learning. Special attention is given to the role of ICT in enhancing language practice, pronunciation, and fluency. The findings suggest that integrating digital technologies into education significantly supports the development of students’ communicative competence and overall academic performance.